Smart Digital for Mobile Communication Through TVUPI Streaming for Higher Education - Darmawan, Deni; Suryadi, Edi; Wahyudin, Dinn (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This study focuses on smart digital for mobile communication through television streaming. It makes use of the television station located in Universitas Pendidikan Indonesia (UPI) which requires further development. In 2017, research was carried out to develop web streaming and Mobile Audience through Smart Digital Mobile.  However, this study uses a research and development approach comprising of 10 main steps some of which are broadcast programs needed in education and local wisdom. The UPI TV Station gained then complete trust from all segments of viewers from the internal academic community. The content test and ease of access are expected to get an overview of the information needs of campus television by the wider community. The results of this project are as follows : (a) Syllabus and SAP Tools in Education Communication courses; (b) Evaluation of the sustainability programs of TVUPI broadcast based on the web streaming; and (c) Mobile Smart Digital Development in expanding the reach of TVUPI viewers based on web streaming.